Impact of vitamin D on the prognosis after spinal cord injury: A systematic review - Wang, Lei; Gan, Jinlu; Wu, Jingnan; Zhou, Yingchun; Lei, Deqiang (Frontiers in Nutrition, 2023)
Vitamin D (VitD) insufficiency is a worldwide health problem and affects billions of people. Spinal cord injury (SCI) patients seem more susceptible to developing suboptimal levels of VitD. However, the literature regarding its impact on the prognosis of SCI is limited. Thus, in this review, we systematically investigated the published studies via a combination of keywords associated with SCI and VitD in four medical databases (Medline, Embase, Scopus, and Web of Science). All included studies were analyzed, and selected clinical data on the prevalence of VitD insufficiency (serum 25-hydroxyvitamin D < 30 ng/ml) and deficiency (serum 25-hydroxyvitamin D < 20 ng/ml) were collected for further meta-analysis via random effects. Through literature review, a total of 35 studies were eligible and included. The meta-analysis of VitD status (13 studies, 1,962 patients) indicated high prevalence of insufficiency (81.6% [75.7, 87.5]) and deficiency (52.5% [38.1, 66.9]) after SCI. Besides, low levels of VitD were reported to be associated with a higher risk of skeletal diseases, venous thromboembolism, psychoneurological syndromes, and chest illness after injury. Existing literature suggested that supplemental therapy might act as an adjuvant treatment to facilitate post-injury rehabilitation. Non-human experimental studies highlighted the neuroprotective effect of VitD, which was associated with enhancing axonal and neuronal survival, suppressing neuroinflammation, and modulating autophagy. Therefore, the current evidence suggests that the prevalence of VitD insufficiency is high in the SCI population, and low-level VitD may impair functional restoration after SCI. VitD supplemental treatment may have potential benefits to accelerate rehabilitation in mechanistically related processes after SCI. However, due to the limitation of the available evidence, more well-designed randomized controlled trials and mechanism experimental research are still needed to validate its therapeutic effect, elucidate its neuroprotective mechanism, and develop novel treatments.